The Performance of The Guiding Service is Supported by The Skills of The Guiding Officer Case Study: Mandatory Waters for Guiding Class 1 Surabaya - Bacthiar, Trio Ahmat; Rakhman, Rizqi Aini; Yudianto, Prima Yudha; Dahri, Muh. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the performance of guidance services supported by the skills of guide officers in class I mandatory waters of Surabaya, focusing on a case study of Gresik Port managed by BUP PT. Maspion of the Port of Indonesia. The analysis was carried out using five dimensions of SERVQUAL, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results showed that all dimensions obtained an average score of 90%, which is very good. The Tangibles dimension shows that the availability of procedural information and supporting facilities such as VTS (Vessel Traffic Service) is in excellent condition, but cleanliness and neatness can still be improved. In the Reliability dimension, the accuracy of the information from the guide is highly assessed, although the stability of the system and the availability of supporting equipment still have room for improvement. The Responsive Dimension indicates that the officer’s problem-solving abilities are excellent, but the speed of response can be improved. In the Assurance dimension, the guide officer is considered to be able to explain procedures well and maintain the confidentiality of service user information, although compliance with operational standards can still be optimized. The Empathy dimension shows a high level of empathy of the officers, although the understanding of the needs of service users can still be improved. With a total actual score of 2,519 out of an ideal score of 2,800, this study concluded that the performance of guidance services at Gresik Port has gone very well.